Numerical simulation of non-ablative laser texturing of silicon surface with a continuous wave fiber laser - Farrokhi, Hamid (2014)
Silicon is highly transparent to the infrared wavelength, so fiber laser with wavelength of 1090 nm is not regarded as a suitable tool for the purpose of ablation based surface texturing. However, we demonstrate, through finite element thermal analyses of laser irradiated surface, non-ablative texturing of Si surface is possible if suitable laser power and dwell time are used to produce peak temperatures above 1250 K and below the Si melting point of 1690 K. Localized oxidation occurs in the temperature range and results in formation of regularly patterned bumps.